دور مؤشرات التوازن المالي في تقييم الاداء المالي للمؤسسة الاقتصادية(دراسة حالة مؤسسة بالنور للصناعة والخدمات 2016_2018) - الازهاري, قريوي; ياسر, غربي; أكرم, نذير (University of eloued جامعة الوادي, 2020)
" تهدف هذه الدراسة إلى معرفة الدور الفعال للأداء المالي في المؤسسة الاقتصادية باستخدام مؤشرات التوازن المالي لتقيم أدائها المالي ومحاولة تحليلها في مؤسسة الدراسة مؤسسة بالنور للصناعة والخدمات لتحسين وضعيتها المالية وذلك بحساب مؤشرات التوازن المالي لمعالجة إشكالية الموضوع واختبار فرضياته وتم الاعتماد على القوائم المالية المتمثلة في الميزانية ؛ هذه المؤشرات هي التي تساعد المحلل المالي لإصدار الحكم على الوضعية المالية للمؤسسة خلال فترة الدراسة. اعتمادا على المنهج المتبع واستنادا إلى النتائج المتوصل إليها تبين لنا أن أدائها المالي كان جيد نوعا ما وخلصت هذه الدراسة إلى أن الاعتماد على مؤشرات التوازن في عملية تقييم الأداء له أهمية بالغة للمؤسسة من خلال قياس التوازن المالي للمؤسسة.""Summary This study aims to evaluate the financial performance of the economic institution using financial balance indicators, and to address the problem of the topic and test its hypotheses the following problem has been raised, ""What is the role of using financial balance indicators in assessing the financial performance of the economic institution?"" Where the study was dropped on an institution in Al-Noor for Industry and Services for the period between 2016-2018 by relying on the descriptive analytical approach in the theoretical side and a case study in the applied side and was also relying on the financial statements represented in the budget and Excel to analyze and understand the data. Where it was concluded that the institution has achieved a financial balance in most years, that is, positive values ​​in working capital and negative values ​​in the needs of working capital, while the treasury is positive throughout the study period, and this study concluded that relying on balance indicators in the performance evaluation process has importance To the institution by measuring the financial balance of the institution."
مذكرة ماستر محاسبة
Keywords: تقييم, الأداء المالي, مؤشرات التوازن; evaluation, financial performance, balance indicators